Gene Cloning, Purification, and Characterization of a Cold-Adapted Lipase Produced by Acinetobacter baumannii BD5 - Park, I.H., Dong-A University, Busan, Republic of Korea; Kim, S.H., Dong-A University, Busan, Republic of Korea; Lee, Y.S., Dong-A University, Busan, Republic of Korea; Lee, S.C., Dong-A University, Busan, Republic of Korea; Zhou, Yi, Dong-A University, Busan, Republic of Korea; Kim, C.M., Pusan National University, Busan, Republic of Korea; Ahn, S.C., Pusan National University, Busan, Republic of Korea; Choi, Y.L., Dong-A University, Busan, Republic of Korea (Journal of microbiology and biotechnology, 2009)
Acinetobacter baumannii BD5 was isolated from waters of Baek-du mountain, and the lipase gene was cloned using a PCR technique. The deduced amino acid sequence of the lipase and lipase chaperone were found to encode proteins of 325 aa and 344 aa with a molecular mass of 35 kDa and 37 kDa, respectively. The lipase gene was cloned and expressed in Escherichia coli BL21 (trxB) as an inclusion body, which was subsequently solubilized by urea, and then purified using Ni-affinity chromatography. After being purified, the lipase was refolded by incubation at 4℃ in the presence of a 1:10 molar ratio of lipase:chaperone. The maximal activity of the refolded lipase was observed at a temperature of 35℃ and pH 8.3 when p-NP caprate (C10) was used as a substrate; however, 28% of the activity observed at 35℃ was still remaining at 0℃. The stability of the purified enzyme at low temperatures indicates that it is a cold-adapted enzyme. The refolded lipase was activated by Ca²+, Mg²+, and Mn²+, whereas Zn²+ and Cu²+ inhibited it. Additionally, 0.1% Tween 20 increased the lipase activity by 33%, but SDS and Triton X-100 inhibited the lipase activity by 40% and 70%, respectively.